2013
DOI: 10.1007/s11095-013-1010-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iontophoresis, Hydration, and Permeation Enhancers on Human Nail Plate: Infrared and Impedance Spectroscopy Assessment

Abstract: Infrared and impedance spectroscopies were used to investigate the effects of hydration, iontophoresis and chemical enhancer (N-acetyl-L-cysteine) treatment on the healthy human nail.Although significant shifts to higher wavenumbers were observed for the symmetric and asymmetric -CH 2 stretching vibrations, the fact that these changes were essentially the same for the three treatments suggested that they were principally due to hydration alone. Spectral changes associated with amide bonds from nail protein wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…In both cases, the surface cells seem to be close, did not show much disruption (though few apertures were visible), and have not altered the overall integrity of the nail structure. Indeed, the results here signify that the low voltage iontophoresis did not alter the structure of the nail, which is also in agreement with the general observation in constant current iontophoresis [ 62 ].…”
Section: Resultssupporting
confidence: 92%
“…In both cases, the surface cells seem to be close, did not show much disruption (though few apertures were visible), and have not altered the overall integrity of the nail structure. Indeed, the results here signify that the low voltage iontophoresis did not alter the structure of the nail, which is also in agreement with the general observation in constant current iontophoresis [ 62 ].…”
Section: Resultssupporting
confidence: 92%
“…All these graphs in the full frequency range show that the dielectric parameters for wet samples are higher compared to dry samples. In other studies performed with the use of capacitive contact imaging [10] and electrical impedance spectroscopy [12], an increase in the dielectric properties of the nail was also observed along with the increase in the water content in this tissue. As a result of the presence of loosely bound water in a wet nail, two relaxation frequencies f c around 2 and 25 kHz (Fig.…”
Section: Methodsmentioning
confidence: 58%
“…The results of our previous dielectric studies of the nail [4][5][6][7] indicate the key role of water in protecting the ordered crystalline structure of the keratin molecule before the onset of the melting process. In recent years, nails research also deals with the influence of water on the biophysical and chemical structure of this material [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Benzeval et al [66] studied the changes in the IR spectra of nail clippings caused by iontophoresis, N-acetyl-L-cysteine treatment, and hydration. It was observed that with hydration, iontophoresis, and N-acetylcysteine, each of them increased the -CH2 stretching frequencies.…”
Section: Infrared Spectroscopy (Ir)mentioning
confidence: 99%